The role of creativity in mediating the relationship between entrepreneurial passion and entrepreneurial alertness - Montiel Campos, Héctor (Review of Business Management, 2016)
Purpose – The purpose of this paper is to investigate creativity as an intermediate variable existing within the relationship between entrepreneurial passion and entrepreneurial alertness. Design/methodology/approach – This is a quantitative research using a moderated mediation model. A questionnaire is used and the analyses are performed with the answers from 244 people with at least 3 years of professional experience and graduate business studies. The discriminant validity of the variables is revised and a hierarchical regression analysis is performed for the hypotheses test. Findings – Significant relations are obtained with which a positive relationship between entrepreneurial passion and creativity can be confirmed, as well as a positive relationship between creativity and entrepreneurial alertness. However, the results also reported that creativity partially mediates the relationship between entrepreneurial passion and entrepreneurial alertness. Originality/value – The contribution of this research lies on showing empirical evidence of the link between entrepreneurial passion, creativity, and entrepreneurial alertness through the use of measurement scales recently developed. It also presents creativity as an intermediate variable in the entrepreneurial passion-alertness relationship.